Ethnomedicinal plants and practices related to pregnancy, childbirth, and postpartum healthcare of Minangkabau ethnic group, West Sumatra, Indonesia - Marina Silalahi; ARDIAN KHAIRIAH; NISYAWATI NISYAWATI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Silalahi M, Khairiah A, Nisyawati. 2020. Ethnomedicinal plants and practices related to pregnancy, childbirth, and postpartum healthcare of Minangkabau ethnic group, West Sumatra, Indonesia. Biodiversitas 21: 4597-4605. In the Minangkabau ethnic cultures, medicinal plants have been used to treat health problems associated with pregnancy, childbirth, and postpartum period (PCP). The objectives of this study were to (i) document the medicinal plants used during pregnancy, childbirth, and postpartum recovery by Minangkabau ethnics and the associated ethnomedicinal practices, and (ii) identify plants that have the potential to be developed as ingredients to increase the production of breast milk. Data were collected in three villages, namely Guguak Sarai, Taruang Taruang, and Sungai Durian in West Sumatra, Indonesia, by interviewing a total of 141 informants, involving 9 key informants and 132 general respondents. A total of 42 species of medicinal plants were found to be used for PCP healthcare by Minangkabau people. These medicinal plants are used to facilitate childbirth, alleviate menstruation problems, assist recovery after miscarriage, mitigate postpartum hemorrhage, aid in postpartum recovery, and for infant care. A total of 26 species were represented by 9 families i.e. Poaceae (7 species), Arecaceae, Fabaceae, Zingiberaceae (3 species respectively), Euphorbiaceae, Lamiaceae, Meliaceae, Musaceae, and Asteraceae (2 species each). Majority of the used medicinal preparations are administered by drinking (35 species), bathing (4 species), and as a paste (3 species). Use of Musa balbisiana, Carallia brachiata, Lansium domesticum, and Toona sureni for treating problems related to pregnancy, childbirth, and postpartum period need to be further investigated for their phytochemistry and pharmacological properties. Plectranthus ambonicus and Sauropus androgynus are used to increase breast milk production, and further research is needed for standardizing processing and commercialization of these species.